Gary Givens at Necessities and More Christmas tree lot - Sahl, Ted (photographer):::Creator::::::::::::
Gary Givens and two unidentified men pose on hay bales at the Necessities and More Christmas tree lot; a fundraising effort for victims of HIV and AIDS.